Gambaran Kesejahteraan Psikologis pada Lansia yang Terlibat dalam Pengasuhan Cucu: Systematic Literature Review - Muhamad Fauzan Azima; Ulfa Dwi Maysarah; Rahmadianti Aulia (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
The growing aging population is leading more and more older adults to become involved in caring for their grandchildren (grandparenting), a role that is not a typical developmental task in old age. Involvement in this role gives rise to complex psychological dynamics and can affect the psychological well-being of older adults in various ways. This study aims to describe the psychological well-being of older adults involved in grandparenting based on an existing literature review. The method used was a Systematic Literature Review (SLR) with literature searches conducted via Google Scholar, Semantic Scholar, PubMed, and ScienceDirect using the keywords psychological well-being, older adults, grandparenting, and caring for grandchildren. Of the 210 articles identified, 10 met the inclusion criteria and were used as data sources. The synthesis results revealed four main themes: (1) grandparenting is generally associated with a reduction in depressive symptoms and improved mental health, particularly in intensive caregiving accompanied by social support; (2) older adults who care for their grandchildren are generally able to fulfill the six dimensions of psychological well-being according to Ryff (1989) and find meaning in life through this role; and (3) direct interaction with grandchildren serves as the primary source of positive emotions such as love, pride, and happiness, which build the older adults’ psychological resilience. In conclusion, grandparenting can be both a source of meaning in life and a source of psychological stress for older adults, depending on the caregiving context, the availability of social support, and the individual’s emotional regulation abilities. It is hoped that these findings will serve as a consideration for families and professionals in supporting the psychological well-being of older adults who are caring for their grandchildren.